Eksplorasi Nilai Budaya Sipakatau Dalam Pelaksanaan Tugas Kepala Sekolah Pendidikan Dasar - Sumarni Sumarni; Erviana Abdullah; Muhammad Nasir (AL-ASASIYYA: Journal Of Basic Education, 2022)
This study aims to describe the exploration of sipakatau cultural values in the implementation of the principal's duties at SD Negeri 205, Pammana, Wajo Regency, South Sulawesi. This study uses a qualitative approach. The location of this research is SD Negeri 205, Maroanging, Pammana, Pammana District, Wajo Regency, South Sulawesi Province. Data collection techniques through interviews, observation and documentation. Data analysis used descriptive analysis. The results of this study indicate that the exploration of sipakatau cultural values in the implementation of the duties of the principal at SD Negeri 205, Pammana, Wajo Regency, South Sulawesi has been reflected in the implementation of their daily duties, this can be seen from the attitude of the principal who has been able to respect and respect members school without having to look at the condition of the members and respect each other when meeting with members who are older and younger. In addition, the exploration of sipakatau cultural values has also been applied to tasks and functions related to (a) curriculum management; (b) student management, which consists of: student planning, student coaching, evaluation of student programs and activities, and student transfers; (c) management of school and community relations, which consists of: fostering relations with the external public and coaching with the internal public.